Molecular Interaction Analysis of COX-2 Against Aryl Amino Alcohol Derivatives from Isoeugenol as Anti Breast Cancer using Molecular Docking - Zulfa Zuhrufa; Tatang Shabur Julianto (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Breast cancer occurs due to uncontrolled cells proliferation. The Proliferation causes severe inflammatory which can be the initial stages of cancer symptoms. Aryl amino alcohol compounds from isoeugenol derivatives are proposed for the potential drugs of breast cancer. This study was conducted on iso-eugenol derivatives by adding carbonyl groups, hydroxyl groups, halide compounds and amines to determine the effect on anticancer activity through molecular docking studies. The molecular docking approach is carried out to see the interaction of ligands with protein compounds by using the minimized ligand energy bind with protein active site using protein data bank ID 5GMN. The docking result show that IE-Benzanilide-Cl (11) and IE-Benzanilide-OH (10) have the lowest binding energy (−8.3 kcal/mol and −8.6 kcal/mol) compare to another compounds. AdmetSAR computer simulations show that all compounds have very few toxic effects. The use of aryl amino alcohol derivatives (10 and 11) may be suggested as anti-breast cancer drugs. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).